Women and wastes: Study on participation of housewives on plastic waste management in Kecandran, Salatiga, Indonesia - Kevin Eric Andrawina; Ahmad Zulfikri; Tio Roberth Ryan Maranatha; Widhi Handayani (Sustinere: Journal of Environment and Sustainability, 2019)
Plastic waste becomes a global environmental problem that is still difficult to overcome by countries over the world, including Indonesia. In fact, Indonesia is the second largest contributor of plastic waste in the world. This problem is even not only encountered by the countries, but also faced by a small town such as Salatiga, Central Java. To overcome the problem, the society should actively be the pioneer since they are the main producer of plastic waste. However, our previous research showed that the households performed limited efforts to manage the waste, and unexpectedly, any activity of waste collection was preferably motivated by financial reasons. Therefore, this study sheds light on the housewives’ perception on plastic and their awareness in managing waste, especially plastic waste. The data of this quantitative study were gathered by means of interview, survey, observation, and documentation from 96 housewives in 6 RW in Kecandran, Sidomukti Sub-District, Salatiga as the participants. The results showed that approximately 60% of the housewives in Kecandran village, Sidomukti sub-district were able to differentiate which waste belonged to non-biodegradable and biodegradable as well as to understand the negative impact of plastic waste toward the environment. They also participated in managing the plastic waste by sorting them (64.58%), participating in waste banks or Bank Sampah (53.13%), and reducing the plastic waste (64.58%). In addition, 85.42% of them were willing to support the government policy in reducing the use of plastic, and 40% of them participated in the payable plastic policy. The role of Bank Sampah is really important to equip the housewives with environmental knowledge. In terms of the payable plastic policy, however, their understanding is not necessarily followed by the willingness to act, which might be related to different orientations and motives.